KARTUN CERIA (CERITA REMAJA INDONESIA) TENTANG PENDIDIKAN SEKS SEBAGAI PENUNJANG MATERI AJAR SISTEM REPRODUKSI DI SMP - Hafizah Saleh; Binari Manurung; Ely Djulia (Biogenesis, 2021)
This development research aims to determine: (1) Content Feasibility; (2) Feasibility of Presentation, (3) Feasibility of Language (Readability), and (4) Feasibility of Design of Ceria Cartoon Calendar (Indonesian Youth Story) for Junior High School students. The research procedure uses the Thiagarajan development model which consists of four stages (four-D models), namely: define stage, design stage, develop stage and disseminate. The feasibility analysis was carried out using a questionnaire instrument which was assessed by three parties consisting of Expert Validators, Biology Teacher Reviewers, and a Student Perception Questionnaire of the Cheerful Cartoon Calendar (Indonesian Youth Story) Biology Class IX SMP PGRI 24 Medan. Analysis. The results of this study showed that: (1) The Feasibility of the Contents of the Ceria Cartoon Calendar (Indonesian Youth Story) obtained good criteria, (2) the Feasibility of the Presentation of the Cheerful Cartoon Calendar (Indonesian Youth Story) obtained very good criteria, (3) the Feasibility of Language (Readability) Calendar Ceria Cartoon (Indonesian Youth Story) obtained good criteria, and (4) the Feasibility of the Ceria Cartoon Calendar (Indonesian Youth Story) Design Feasibility criteria obtained very good eligibility criteria. The results of this study imply that the Ceria Cartoon Calendar (Indonesian Youth Story) Biology has good criteria to be used for adolescent students, especially in class IX SMP in conveying information about knowledge about sex education in supporting reproductive system materials in the classroom.